Epithelial/mesenchymal plasticity: how have quantitative mathematical models helped improve our understanding?. Issue 7 (19th June 2017) - Jolly, Mohit Kumar; Tripathi, Satyendra C.; Somarelli, Jason A.; Hanash, Samir M.; Levine, Herbert
Abstract : Phenotypic plasticity, the ability of cells to reversibly alter their phenotypes in response to signals, presents a significant clinical challenge to treating solid tumors. Tumor cells utilize phenotypic plasticity to evade therapies, metastasize, and colonize distant organs. As a result, phenotypic plasticity can accelerate tumor progression. A well‐studied example of phenotypic plasticity is the bidirectional conversions among epithelial, mesenchymal, and hybrid epithelial/mesenchymal (E/M) phenotype(s). These conversions can alter a repertoire of cellular traits associated with multiple hallmarks of cancer, such as metabolism, immune evasion, invasion, and metastasis. To tackle the complexity and heterogeneity of these transitions, mathematical models have been developed that seek to capture the experimentally verified molecular mechanisms and act as 'hypothesis‐generating machines'. Here, we discuss how these quantitative mathematical models have helped us explain existing experimental data, guided further experiments, and provided an improved conceptual framework for understanding how multiple intracellular and extracellular signals can drive E/M plasticity at both the single‐cell and population levels. We also discuss the implications of this plasticity in driving multiple aggressive facets of tumor progression. Abstract : In this review, we highlight how an integrated theoretical‐experimental approach has driven a better understanding of epithelial/mesenchymal (E/M) plasticity. Through multiple examples presented in a pedagogical manner, we discuss how quantitative mathematical models focused on signaling networks and/or cellular mechanics have acted as hypothesis‐generating tools to guide further experiments to decode multiple aspects associated with E/M plasticity, such as stemness, motility, immune evasion, and drug resistance. We also suggest what other open questions in the regulation of epithelial‐mesenchymal transition and mesenchymal‐epithelial transition can benefit from bidirectional communication among quantitative mathematical in silico models and diverse in vitro and in vivo experiments.